(untitled) (Pakistan Journal of Kidney Diseases, 2021)
We present a case of a 61 years old male patient with tuberculous meningitis (TBM) had polyuria, hypernatremia with high fractional excretion of sodium, low serum uric acid with high FEUA & clinically evident dehydration. A diagnosis of cerebral salt wasting (CSW) secondary to TBM was made based on laboratory and clinical parameters. Patient was treated with ATT, fluid replacement with normal saline and fludrocortisone therapy and recovered. We have discussed the case and reviewed the literature review.